Balanced Transmissions Based Trajectories of Mobile Sink in Homogeneous Wireless Sensor Networks. (20th February 2017) - Akbar, Mariam; Javaid, Nadeem; Abdul, Wadood; Ghouzali, Sanaa; Khan, Abid; Niaz, Iftikhar Azim; Ilahi, Manzoor
Abstract : Mobile Sink (MS) based routing strategies have been widely investigated to prolong the lifetime of Wireless Sensor Networks (WSNs). In this paper, we propose two schemes for data gathering in WSNs: (i) MS moves on random paths in the network (RMS) and (ii) the trajectory of MS is defined (DMS). In both the schemes, the network field is logically divided into small squares. The center point of each partitioned area is the sojourn location of the MS. We present three linear programming based models: (i) to maximize network lifetime, (ii) to minimize path loss, and (iii) to minimize end to end delay. Moreover, a geometric model is proposed to avoid redundancy while collecting information from the network nodes. Simulation results show that our proposed schemes perform better than the selected existing schemes in terms of the selected performance metrics.